Manufacturing and Characterization of Few—Layered Graphene Reinforced Acrylonitrile Butadiene Styrene Thermoplastic Composites by the Fused Deposition Modelling - Aydin, Hurşit Sefa; Gümüş, Omer Yunus; Uzunsoy, Deniz (Springer Nature, 2025)
In recent years, additive manufacturing (AM) technologies have become a production technique used in many areas of industry. Among the AM technologies, Fused Deposition Modelling (FDM) technique is one of the best known and most widely used three-dimensional (3D) production methods. Especially, the improvement of the mechanical, electrical, thermal and tribological properties of composites produced by reinforcing nanoparticles into the thermoplastic matrix structure increases the use of the FDM technique. In this study, composite filaments obtained by reinforcing acrylonitrile butadiene styrene (ABS) with 0.75 weight ratio of commercial graphene and few-layered graphene (FLG) were printed three-dimensionally using FDM technique. The used graphene was synthesized by electric arc discharge as high-purity few-layer graphene (FLG). Additionally, the resulting composite filaments were produced by twin-screw and single-screw extrusion. Effect of graphene on the ABS matrix structure was investigated by performing chemical, thermal and mechanical properties and characterizations of the structures produced by 3D printing. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: ABS; Additive manufacturing; FDM; FLG; Graphene